Оптимизация состава фондов библиотек высшей школы Литвы - Янулявичене, Альма (Knygotyra, 1991)
The optimisation of stocks composition is possible only in complex way improving the stocks of republic higher school libraries. The optimisation of each library stocks structure needs: to draw up topical subject completing program and to encrease the quality literature selection; to mark out the kernal of library stock and to organize rationally the work of it; to determine the criterion of little used literature delimitation and to organize separate storage if needed; to create the system of inverse connection with the reader based upon the constant research of turnover stocks and literature refusal. The creation of rational republic system of higher school libraries stocks needs: to compose the plan of coordination complecting stocks of each higher school libraries on the basis of topical complecting stock plans; to compose the coordinate storage plan of little used literature and to organize it’s work with taking in response to all the higher school system. The formation of stocks consists of several processes (the determinaiton of information needs, the composition of the topical plans, complecting the selection of literature into basic and secondary stocks, analyses of data about stocks structure and use) which form the information stock system. The analysis of topical completing plans has shown, that they consist of data about the completing topic, types and kinds of literature and copies. Now the topical plan completing coordinate stocks plan is preparing on the basis of topical completing plans. The researches have shown, that in order to make the coordinate campleting stocks plan at first is needed to create the topical completing plan in an higher school libraries by united methods.